Combining Economic and Political Development The Experience of MENA - Luciani, Giacomo (International Development Policy, 2017)
Democratic transitions since 2011 in the Middle East and North Africa have mostly failed to consolidate and have been hindered by the difficult economic heritage of previous authoritarian governments. Which short-term economic policies may help consolidate the early democratisation process? Readership: Scholars and policy makers interested in MENA, democratic transition, economic and political development, reform and regional integration.